Performance Assessment of Base Plate Connections with Anchor Rod Sleeves - Atar, Muhammed; Sayın, Erkut (My University, 2024)
This research presents findings from a study focused on evaluating the performance of exposed base plate connections featuring anchor rods under cyclic loading conditions. The study introduces an innovative sleeve system approach designed to enhance the ductility of column base connections. The inclusion of a steel sleeve with defined geometric characteristics between the base plate and the anchor rod washer modifies the load path within the connection, resulting in a more ductile response. The study utilizes a validated finite element (FE) model to analyze exposed base plate connections featuring different sleeve shapes, illustrating the concept behind this novel method. The innovative approach discussed in this research has the potential to significantly increase the rotational capacity of connections without compromising their inherent strength.
Keywords: Cyclic loading; Retrofitting; Base plate connection; Ductility; Rotational capacity